Cultural Offer and Distance in a Spatial Interaction Model for Tourism - Roberto Patuelli; Maurizio Mussoni; Guido Candela (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2014)
Culture is more and more considered as an important driver of tourism. However, it is critical, for policymakers, to evaluate the potential returns from investments in culture and generally cultural offer, in particular in multiregion settings with a potentially inefficient distribution of cultural offer. Our paper focuses on the role of distance (between the tourist's origin and destination regions) in mediating the tourism impact of cultural offer. This research question is investigated by means of a spatial interaction model, applied to the case of Italian domestic tourism. We find that distance indeed matters: a destination's endowment in culture appears to be more attractive for long-distance tourists, while an origin region's endowment seems to dinsincentivate long-distance trips to a greater extent.
Keywords: C23; L83; R12; Z10; 330